Comparison between normal coffee and decaffeinated coffee effects on lymphocytes and macrophages: role of antioxidant activity of caffeine - Davicino, Roberto Carlos (2009)
Coffee (Coffea arabica L.) presents antioxidant effects. Due to negative effects of caffeine (Ca), more people consume decaffeinated coffee. Reactive oxygen species are involved in immune cell physiology controlling proliferation, death and cellular metabolism. The aim of this study was to evaluate the influence of Ca in the effect of normal and decaffeinated coffee on normal mice lymphocytes and macrophages. It were assayed MTT, nitroblue tetrazolium reduction, proliferation assays and superoxide and catalase‐like activities were determined. The decaffeinated coffee induced a decrease in lymphocytes proliferation in all concentrations assayed; this effect was related to an increase of superoxide anion and with the absence of Ca, which by itself increased lymphocytes proliferation through a decrease in H2O2 level by CAT activity “per se.” On macrophages, both extracts induced cell activation not related to the presence of Ca. In conclusion, caffeinated coffee could be better than decaffeinated coffee in the maintenance of the oxidative balance in lymphocytes cells.